The main article of the Treaty on the Eurasian Economic Union, dedicated to customs issues (Journal of actual problems of jurisprudence, 2018)
This article discusses some of the main articles of the Treaty on the Eurasian Economic Union, dedicated to customs issues. Within the framework of the Customs Union member states apply the common customs tariff of the Eurasian Economic Union and other common measures regulating foreign trade in goods with third parties; is a single trade regime in relation to third parties and implemented a single customs regulation. Key words: Treaty on the Eurasian Economic Union, customs regulation in the Eurasian Economic Union